Elevated Plasma microRNA-206 Levels Predict Cognitive Decline and Progression to Dementia from Mild Cognitive Impairment - Kenny, Aidan (Biomolecules, 2019)
The need for practical biomarkers for early diagnosis of Alzheimer’s disease (AD) remains largely unmet. Here we investigated the use of blood-based microRNAs as prognostic biomarkers for AD and their application in a novel electrochemical microfluidic device for microRNA detection. MicroRNA transcriptome was profiled in plasma from patients with mild cognitive impairment (MCI) and AD. MicroRNAs Let-7b and microRNA-206 were validated at elevated levels in MCI and AD, respectively. MicroRNA-206 displayed a strong correlation with cognitive decline and memory deficits. Longitudinal follow-ups over five years identified microRNA-206 increases preceding the onset of dementia. MicroRNA-206 was increased in unprocessed plasma of AD and MCI subjects, detected by our microfluidic device. While increased Let-7b levels in plasma may be used to identify patients with MCI, changes in plasma levels of microRNA-206 may be used to predict cognitive decline and progression towards dementia at an MCI stage. MicroRNA quantification via a microfluidic device could provide a practical cost-effective tool for the stratification of patients with MCI according to risk of developing AD.